COVID-19 aerosol box as protection from droplet and aerosol contaminations in healthcare workers performing airway intubation: a randomised cross-over simulation study - Muhaimin, Noor Azhar; Aida, Bustam; Khadijah, Poh; Ahmad Zulkarnain, Ahmad Zahedi; Mohd Zahir Amin, Mohd Nazri; Mohammad Aizuddin Azizah, Ariffin; Mohd Hafyzuddin, Md Yusuf; Aliyah, Zambri; Chong, Johnathan Y O; Anhar, Kamarudin; Ang, Bin Ting; Affan, Iskandar; et al. (BMJ Publishing Group, 2020)
Background Concerns over high transmission risk of SARS-CoV-2 have led to innovation and usage of an aerosol box to protect healthcare workers during airway intubation in patients with COVID-19. Its efficacy as a barrier protection in addition to the use of a standard personal protective equipment (PPE) is not fully known. We performed a simulated study to investigate the relationship between aerosol box usage during intubation and contaminations on healthcare workers pre-doffing and post-doffing of PPE.